Conception et comportement dynamiques des structures de génie civil : application aux ouvrages paravalanches Behaviour and design of civil engineering structures exposed to dynamic loads: the case of snow avalanches defence works - Jean-Marc Tacnet, Emmanuel Thibert, Philippe Berthet-Rambaud, Ali Limam, Mohamed Naaim, Pascal Perrotin et Didier Richard (Sciences, Eaux & Territoires, 2010)
Optimiser la conception des ouvrages de protection contre les avalanches est une priorité pour la sécurité en montagne. Les auteurs nous démontrent ici comment la discipline du génie civil contribue à améliorer les connaissances sur le comportement des ouvrages rigides de protection face aux différentes pressions exercées par les avalanches. This article proposes an easy understandable synthesis of main principles related to the physical behaviour of civil engineering structures impacted by snow avalanches. Improving knowledge of pressure due to an avalanche on a civil structure is an essential step to design resisting protection works. In situ experimental devices using structures as macro-sensors is an original and innovative way that complete the existing research approaches mainly based on hydrodynamics and fluid mechanics principles. General principles for design and building for rigid civil engineering works are presented. At the end, operational recommendations are proposed to improve the dynamic loads and therefore global risk assessments.